The effect of alumina additive and sintering temperature on the microstructural, physical, mechanical, and bioactivity properties of hydroxyapatite-alumina composites - SALMAN, SERDAR; PAZARLIOĞLU, SÜLEYMAN SERDAR (SPRINGER, 2020)
The aim of this study was to evaluate the effect of alumina (Al2O3) additive and sintering temperature on the microstructural, physical, mechanical, and in vitro bioactivity properties of hydroxyapatite (HA). The composites consisting of 2.5 and 5 wt% Al2O3 and monolithic HA were uniaxially pelleted at 350 MPa with the size of null 11 and 11 mm(2) and sintered at five different temperatures ranging from 900 to 1300 degrees C for 4 h. A series of thermal analysis methods and tests were used to evaluate both phase changes that occurred during sintering and the physical/mechanical properties of the sintered samples. The bioactivity property of the samples having the highest compressive strength value was investigated in a simulated body fluid (SBF) solution for 3, 7, 15, and 30 days. Results showed that HA without Al2O3 had started to decompose at 1200 degrees C, and the addition of Al2O3 led to the reduction of decomposition temperature from 1200 to 900 degrees C. However, the main phase was HA for all the sintered samples. The highest mechanical strength values were 130.20 +/- 6.22, 60.27 +/- 9.93, and 0.96 +/- 0.05 MPa m(1/2) for compressive strength, three-point bending strength, and fracture toughness, respectively, for monolithic HA when it was sintered at 1100 degrees C. All of these mechanical strength values of monolithic HA were improved higher than the rate of 60% as the grain growth of HA was inhibited by the addition of Al2O3. The highest mechanical strength values of HA-Al2O3 composites were obtained for the samples sintered at 1200 degrees C when the densification rate reached 90%. In vitro investigations showed that Al2O3 led to a reduction in the in vitro bioactivity of HA, but it could be used in the human body since its surface is coated by apatite layers when in vitro time reached 30 days.
Keywords: Hydroxyapatite; Alumina; Sintering; TRICALCIUM PHOSPHATE; CALCIUM ALUMINATE; IN-VITRO; FRACTURE-TOUGHNESS; PARTICLE-SIZE; BEHAVIOR; CERAMICS; PRESSURE; PHASE; BIOCERAMICS